Associations of early-life exposure to famine with abdominal fat accumulation are independent of family history of diabetes and physical activity. Issue 8 (28th April 2021) - Hu, Xiang; Wen, Junping; Yu, Weihui; Yang, Lijuan; Pan, Wei; Xu, Ke; Chen, Xueqin; Li, Qianqian; Chen, Gang; Gu, Xuejiang
Abstract: The present study aimed to investigate the association of early-life exposure to famine with abdominal fat accumulation and function and further evaluate the influence of first-degree family history of diabetes and physical activity on this association. The present work analysed parts of the REACTION study. A total of 3033 women were enrolled. Central obesity was defined as waist circumferences (W) ≥ 85 cm. Chinese visceral adiposity index (CVAI) was used to evaluate visceral adipose distribution and function. Partial correlation analysis showed BMI, W, glycated Hb and CVAI were associated with early-life exposure to famine (both P < 0·05). Logistic regression showed that the risks of overall overweight/obesity and central obesity in fetal, early-childhood, mid-childhood and late-childhood exposed subgroups were increased significantly (all P < 0·05). Compared with the non-exposed group, the BMI, W and CVAI of fetal, early- to late-childhood exposed subgroups were significantly increased both in those with or without first-degree family history of diabetes and in those classified as physically active or inactive, respectively (all P < 0·05). The associations of BMI, W and CVAI with early-life exposure to famine were independent of their associations with first-degree family history of diabetes (all P < 0·01) or physical activity status (all P < 0·001). Early-life exposure to famine contributed to abdominal fat accumulation and dysfunction, which was independent of the influence of genetic background and exercise habits. Physical activity could serve as a supplementary intervention for women with high risk of central obesity.